Validity evidence for Quality Improvement Knowledge Application Tool Revised (QIKAT-R) scores: consequences of rater number and type using neurology cases. Issue 11 (17th April 2019) - Kassardjian, Charles; Park, Yoon Soo; Braksick, Sherri; Cutsforth-Gregory, Jeremy; Robertson, Carrie; Young, Nathan; Leep Hunderfund, Andrea
Abstract : Objectives: To develop neurology scenarios for use with the Quality Improvement Knowledge Application Tool Revised (QIKAT-R), gather and evaluate validity evidence, and project the impact of scenario number, rater number and rater type on score reliability. Methods: Six neurological case scenarios were developed. Residents were randomly assigned three scenarios before and after a quality improvement (QI) course in 2015 and 2016. For each scenario, residents crafted an aim statement, selected a measure and proposed a change to address a quality gap. Responses were scored by six faculty raters (two with and four without QI expertise) using the QIKAT-R. Validity evidence from content, response process, internal structure, relations to other variables and consequences was collected. A generalisability (G) study examined sources of score variability, and decision analyses estimated projected reliability for different numbers of raters and scenarios and raters with and without QI expertise. Results: Raters scored 163 responses from 28 residents. The mean QIKAT-R score was 5.69 (SD 1.06). G-coefficient and Phi-coefficient were 0.65 and 0.60, respectively. Interrater reliability was fair for raters without QI expertise (intraclass correlation = 0.53, 95% CI 0.30 to 0.72) and acceptable for raters with QI expertise (intraclass correlation = 0.66, 95% CI 0.02 to 0.88). Postcourse scores were significantly higher than precourse scores (6.05, SD 1.48 vs 5.22, SD 1.5; p < 0.001). Sufficient reliability for formative assessment (G-coefficient > 0.60) could be achieved by three raters scoring six scenarios or two raters scoring eight scenarios, regardless of rater QI expertise. Conclusions: Validity evidence was sufficient to support the use of the QIKAT-R with multiple scenarios and raters to assess resident QI knowledge application for formative or low-stakes summative purposes. The results provide practical information for educators to guide implementation decisions.